A study on the relationship between online advertisement and purchase intention among Generation Y in Universiti Teknologi Mara (UiTM) Pulau Pinang / Nor Azliana Norli - Norli, Nor Azliana (Faculty of Business and Management, 2016)
The objectives of this study and the research questions of the study have been attempted and answered accordingly. It is concluded that all hypotheses were tested and significant levels were presented and conclusions made. The significant variables identified and their relationships between online advertisements influence to Generation Y consumer's purchase intention with personal characteristics like age, gender, marital status, education, income, and etc., quality advertisement of products and services and consumer perception were in general positive and significantly affected. On the other hand, the hypotheses were accepted in the differences in consumer purchasing factors when considering income and occupation between Generation Y customers' to purchasing decision of products in Universiti Teknologi MARA (UiTM) Pulau Pinang. Majority of the respondents after viewing advertisements, were motivated to buy products and services based on the quality in relation with price and consumer perception with product fashion and limited editions with exceptional technological features, which shows that Generation Y consumers' purchase decisions have the mixed combination of their own behaviour and social implications which is to bring up their social status in their community. Since these ranges of population transferring to more important consumer group as a result of their perceptions of online advertisements credibility, organizations and media planners are paying more attention to these types of customers.